Laurence Coffelt: Cassoday, 1910-1976 - Lawrence P. Klintworth (Symphony in the Flint Hills, 2014)
Long before Laurence Coffelt, a Kansas farm boy from the Flint Hills, was born, the last of the Longhorn cattle had made their journey north up the old Chisholm Trail. Deep ruts of the historic cattle trails had been cross-fenced with barbed wire and plowed under by the generation in which Coffelt lived, but some Old Timers still lived who remembered the Open Range.
Keywords: farm boy; Laurence Coffelt; trails; longhorn; cattle; Open Range; animals; rodeo; cowhands